Analisis Pengaruh Jenis -Jenis Rumah Ekonomi dalam Meningkatkan Pemahaman Siswa SMAN 12 Medan - David Christian Silitonga; Nurul Mardiah; Romauli Situmeang; Revita Yuni; Siti Sarah Tumangger (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Economic concepts are often considered abstract and difficult to understand by high school students. The lack of connection between the subject matter and the reality of everyday life is one of the factors causing low student interest in learning in this field. This study aims to explore the effectiveness of the "home economics" learning approach in improving students' understanding of the economic system. The study was conducted at SMAN 12 Medan using a quantitative method with a questionnaire instrument that has been tested for validity and reliability. The results showed that this approach was able to explain 59.2% of the variation in students' understanding of economics. This study suggests that teachers use contextual learning models to improve the effectiveness of the economics learning process.